Propuesta a la reforma del art. 127, sobre la sanción penal en la negligencia, impericia, imprudencia, exeso de velocidad, conocimiento de daños mecanicos e inobservacia de la ley de transito. - Vintimilla Castro, Galo (2012)
The present thesis is the "PROPOSAL TO ART'S REFORMATION. 127, ON THE PENAL SANCTION IN THE NEGLIGENCE, IMPERICIA, IMPRUDENCE, EXESO OF SPEED, KNOWLEDGE OF MECHANICAL DAMAGES AND INOBSERVACIA OF THE LAW OF I TRAFFIC", he/she has as purpose the improvement of the circulation vial, in order to avoid the commission of great quantity of traffic crimes, since this type of infractions has the character of preventive and when making it it is also possible to diminish the traffic accidents. It is therefore indispensable to know the universe of the infractions that according to the new Organic Law of Traffic and their Regulation establishes sanctions so much for drivers as much as it stops pedestrians that make radical necessary changes in the daily attitudes of the citizens. This work understands the revision of the statistics of infractions of traffic in a general way; a study on the character compose of the traffic infractions; boat to the traffic infractions in its different classes and its judged. The methodology used for the realization of the work was mainly descriptive, using the deductive-inductive method, taking into account the national problem to focus it in the city of Loja; he/she was carried out surveys to people's groups that are immerses in the development and application of the traffic law.